Impact of Cytotoxic T Lymphocyte (CTL) escape mutations in acute/Early HIV-1 Subtype C Infection on Disease Progression - Chopera, Denis Rutendo (Division of Virology, 2014)
Includes abstract. Includes bibliographical references (leaves 139-162).